Reengineering of business processes in the context of application of new organizational schemes of construction management - S. B. Sborschikov; N. V. Lazareva (Vestnik MGSU)
Introduction. The current state of investment and construction activities at the corporate level is determined not only by the complexity of applied engineering solutions of capital construction facilities, but also by changes in a similar trend of external and internal environments of economic entities involved in the construction of a building or structure. Such complication is caused by the permanent increase of scientific and technological progress and the manifestation of economic phenomena corresponding to it, which affect the demands of consumers and regulatory rules of the state. As a result, there is an increase in contradictions between the conditions for the implementation of investment and construction activities and the organization of construction management, which is the reason for the emergence of new options for the implementation of business processes, their addition and integration with production and security processes, i.e. the emergence of new organizational schemes for construction management. One of these schemes can be used to manage construction on the basis of production and engineering centre. As noted in the paper, the main direction of increasing efficiency in this organizational structure is the transformation of management processes, i.e. their reengineering.Materials and methods. The research is based on the postulates of cybernetics, the logistics of regulatory influences, the organization of production systems, and structural and functional analysis. The scientific background of the authors was used, which was reflected in their publications on this problem. Additional sources were scientific works of domestic and foreign scientists in this subject area.Results. The structure and composition of the production and engineering centre are substantiated, the distribution of the main groups of functions is performed, the place of such an organizational structure in the corporate management system of investment and construction activities is determined, and the directions of business process reengineering are established.Conclusions. The formation of new, modern organizational structures is a promising direction of business process reengineering to increase the efficiency of construction, improve the quality of construction products, as well as the interaction of participants of investment and construction activities.